Validation of a Technological Pedagogical Content Knowledge Instrument in a Malaysian Secondary School Context - Hasniza Nordin; Tengku Faekah Tengku Ariffin (UUM Press, 2016)
Purpose â€" This study focused on the validation of a Technological Pedagogical Content Knowledge (TPACK) instrument for using ICT in teaching and learning effectively in a Malaysian secondary school setting. The aim of this study was to confirm a seven-factor TPACK model which includes Technological Knowledge, Content Knowledge, Pedagogical Knowledge, Pedagogical Content Knowledge, Technological Pedagogical Knowledge, Technological Content Knowledge and Technological Pedagogical Content Knowledge.   Methodology â€" This study was designed as a case study situated within a particular context in Malaysia. A survey was administered to 150 pre-service teachers enrolled in a university in Malaysia. Confirmatory factor analysis (CFA) of the adapted TPACK survey was preceded by assessing the fit of the measurement model with the data in the study based on the a priori theoretical model.   Findings â€" The findings revealed that the measurement model adequately fit with the data collected within a Malaysian secondary school context, also lending validity to the adapted TPACK instrument used in this study.   Significance â€" The adapted and translated TPACK survey was found to be a valuable self-report instrument for measuring pre-service teachersâ€™ TPACK knowledge. A greater understanding of TPACK may be required for pre-service teachers before adequate gains in using ICT in teaching can be achieved. Thus, it is recommended that this knowledge should be integrated in the Initial Teacher Education curriculum with more attention to improving access to ICT in Initial Teacher Education and the schools.